Influence of Social Media on Political Orientation - Chaudhary, Harsh (Digital Repository of Theses, 2025)
This research sought to uncover connections among political media, public sentiment, and social media usage, and additionally aimed to determine how political media shape's public opinion in various contexts and across demographics. Nowadays, information is exchanged in new ways, and campaign strategies have dramatically shifted and significantly evolved since India’s 2014 general election. With the goal of reaching more people and winning more votes, the majority of prominent political groups have moved their campaign operations online. At this point in time, all of the main political parties in India use social media to spread their electoral outreach messages. The present investigation delves into the connection between political identification and social media, revealing how these elements impact people’s political opinions, engagement with news stories, and the beliefs they embrace across time. Furthermore, the investigation examines how social media affects users, including the increasingly rapid and extensive dissemination of data that fosters echo chambers and the propagation of false or misleading content online.